Tumor targeting by lentiviral vectors combined with magnetic nanoparticles in mice. (1st September 2017) - Borroni, Ester; Miola, Marta; Ferraris, Sara; Ricci, Giulia; Žužek Rožman, Kristina; Kostevšek, Nina; Catizone, Angela; Rimondini, Lia; Prat, Maria; Verné, Enrica; Follenzi, Antonia
Graphical abstract: Abstract: Nanomaterials conjugated or complexed with biological moieties such as antibodies, polymers or peptides appear to be suitable not only for drug delivery but also for specific cancer treatment. Here, biocompatible iron oxide magnetic nanoparticles (MNPs) with or without a silica shell coupled with lentiviral vectors (LVs) are proposed as a combined therapeutic approach to specifically target gene expression in a cancer mouse model. Initially, four different MNPs were synthesized and their physical properties were characterized to establish and discriminate their behaviors. MNPs and LVs strictly interacted and transduced cells in vitro as well as in vivo, with no toxicity or inflammatory responses. By injecting LV-MNPs complexes intravenously, green fluorescent protein (GFP) resulted in a sustained long-term expression. Furthermore, by applying a magnetic field on the abdomen of intravenous injected mice, GFP positive cells increased in livers and spleens. In liver, LV-MNPs were able to target both hepatocytes and non-parenchymal cells, while in a mouse model with a grafted tumor, intra-tumor LV-MNPs injection and magnetic plaque application next to the tumor demonstrated the efficient uptake of LV-MNPs complexes with high number of transduced cells and iron accumulation in the tumor site. More important, LV-MNPs with the application of the magnetic plaque spread in all the tumor parenchyma and dissemination through the body was prevented confirming the efficient uptake of LV-MNPs complexes in the tumor. Thus, these LV-MNPs complexes could be used as multifunctional and efficient tools to selectively induce transgene expression in solid tumor for therapeutic purposes. Statement of Significance: Our study describes a novel approach of combining magnetic properties of nanomaterials with gene therapy. Magnetic nanoparticles (MNPs) coated with or without a silica shell coupled with lentiviral vectors (LVs) were used as vehicle to target biological active molecules in a mouse cancer model. After in situ injection, the presence of MNP under the magnetic field improve the vector distribution in the tumor mass and after systemic administration, the application of the magnetic field favor targeting of specific organs for LV transduction and specifically can direct LV in specific cells (or avoiding them). Thus, our findings suggest that LV-MNPs complexes could be used as multifunctional and efficient tools to selectively induce transgene expression in solid tumor for therapeutic purposes.